The Mediating Role of Tax Morale in the Relationship Between Perceived Fairness, Trust in Government, and Voluntary Tax Compliance - Primandita Fitriandi; Andri Marfiana; Arief Budi Wardana; Imaduddin Zauki (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study examines whether tax morale mediates the relationship between perceived fairness, trust in government, and voluntary tax compliance among non-employee individual taxpayers in Indonesia. Methods – A quantitative explanatory design was applied using survey data from 211 non-employee individual taxpayers in the Greater Jakarta area. The data were analyzed using SmartPLS 4 and partial least squares structural equation modeling. Findings – Perceived fairness, trust in government, and tax morale have positive and significant direct effects on voluntary tax compliance among taxpayers in Greater Jakarta. However, perceived fairness and trust in government do not significantly influence tax morale. The trust-to-tax-morale path shows a negative but statistically insignificant coefficient. Specific indirect effects also indicate that tax morale does not mediate the relationships between perceived fairness, trust in government, and voluntary tax compliance. Implications – Voluntary compliance appears to be shaped more by direct institutional perceptions and intrinsic moral motivation than by a sequential mediation mechanism. Policymakers should strengthen fairness, accountability, transparency, and service quality while developing tax education that reinforces moral awareness. Originality – This study contributes to behavioral taxation research by showing that institutional perceptions and tax morale may operate as parallel determinants of voluntary tax compliance in Indonesia’s self-assessment tax system.